Parenting Styles and its Effect on Children - Karunakaran, Deepthi; George, Jomet (Innovational: Journal of Nursing and Healthcare, 2024)
The term parenting has been defined as the process or the state of being a parent and includes nourishing, protecting, and guiding a child through the course of development. The parenting style is the attitude that parents express to their kids. It can be affected by numerous factors, including social, cultural, political, economic, etc. It is affected by both the parents’ and children’s temperaments and is chiefly based on the impact of one’s own parents and culture. Positive parenting helps the child face non-social or social problems. Positive parenting is required for early cognitive development, emotional balance, and the maturation of thought. While negative, hostile parenting leads to depression and social and cultural problems. Every parent has a different approach to how to interact and guide their children. Achild’s morals, principles, and conduct are generally established through this bond. Every category employs a unique approach to how parents raise their children. In general, each parent will fall into one of these categories and sometimes have some characteristics from another category. Parenting style can also be situation-dependent. Research has explored the influence of parenting on a number of outcomes for children, including behavior problems, mood difficulties, and academic success. In general, studies find that parenting characterized by warmth, nurture, and limit setting is helpful in promoting positive outcomes for youth. This review article analyzes the influence of parents and their parenting styles on children’s behavior. The article looks at several different parenting styles and the effects it brings over different aspects of children’s lives.